Analysis of the Impact of Fiscal Policy on Economic Growth in Indonesia - Rezki Akbar Norrahman (Journal of Scientific Interdisciplinary, 2024)
This research investigates the impact of fiscal policy on economic growth in Indonesia. The study was carried out by analyzing the implementation of public expenditure policies, tax reforms and subsidies implemented by the government in several time periods. Macroeconomic data such as Gross Domestic Product (GDP), inflation rate, investment and household consumption are used to evaluate the effectiveness of fiscal policy in responding to domestic and global economic conditions. The findings show that fiscal policy has a significant impact on economic growth, particularly through increasing infrastructure investment and tax incentives for the private sector. However, challenges such as transparent public budget management and long-term policy consistency need to be addressed to maximize the contribution of fiscal policy to inclusive and sustainable economic growth. Policy recommendations include expanding infrastructure investment, further tax reform to increase efficiency, as well as improvements in public budget management. The implication of this research for national economic policy is the importance of maintaining policy consistency and improving inter-institutional coordination to achieve the goal of sustainable economic development in Indonesia.